Anglo-Ottoman Encounters in the Age of Revolution
1 online resource (368 pages)
Keywords: This volume traces the effects of involvement in the Revolutionary and Napoleonic Wars on the Ottoman Empire. The book analyzes Anglo-Ottoman relations in a series of studies of five British ambassadors at Constantinople and one Foreign Secretary, George Canning.